The strange case of Origami Yoda - Angleberger, Tom. (New York : Amulet Books, 2010)
Sixth-grader Tommy and his friends describe their interactions with a paper finger puppet of Yoda, worn by their weird classmate Dwight, as they try to figure out whether or not the puppet can really predict the future. Includes instructions for making Origami Yoda.
Wilson's Children, October 2010.
Wilson's Junior High School, September 2011.
Notable/Best Books (A.L.A.), January 2011.
School Library Journal, May 2010.
Publisher's Weekly, March 2010.
Booklist, May 2010.
Keywords: Finger puppets -- Juvenile fiction; Origami -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Finger puppets -- Fiction; Origami -- Fiction; Eccentrics and eccentricities -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Schools -- Fiction